Broken promises: Regime announcements and exchange rates around elections - Pablo Garofalo; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
We study the relationship between exchange-rate regime announcements and exchange-rate dynamics around government changes by combining the IMF de jure and the Reinhart and Rogoff de facto exchange-rate regime classifications. Using monthly data from Latin American democracies, we do not identify significant exchange-rate depreciations before the change of government in any of the regimes, but we do identify a gradual exchange-rate overvaluation when regimes are fixed inconsistent (i.e., the de jure regime announcement is fixed and differs from the de facto behavior). After the change of government, the overvaluation under fixed-inconsistent regimes is abruptly corrected through significant devaluations. We thus identify a pattern of broken promises by which incumbents delay devaluations until after the change of government under fixed-inconsistent announcements, but not under fixed-consistent ones. Controlling for conditional volatility, we also detect significant "fear of floating" in flexible-inconsistent regimes before the change of government, when electoral stakes are highest.
Keywords: D72; D78; E00; 330; exchange-rate regimes; exchange-rate overvaluations; electoral cycles